2004
DOI: 10.1016/j.bbaexp.2004.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression in the bovine corpus luteum through generation and characterisation of 960 ESTs

Abstract: To gain new insights into gene identity and gene expression in the bovine corpus luteum (CL) a directionally cloned CL cDNA library was constructed, screened with a total CL cDNA probe and clones representing abundant and rare mRNA transcripts isolated. The 5V-terminal DNA sequence of 960 cDNA clones, composed of 192 abundant and 768 rare mRNA transcripts was determined and clustered into 351 non-redundant expressed sequence tag (EST) groups. Bioinformatic analysis revealed that 309 (88%) of the ESTs showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…IGFBP-related protein 1 (or IGFBP-7) has been found to have an important role in the female reproductive system. It was implicated in human endometrial receptivity, folliculogenesis as well as growth, development, and regression of the corpus luteum in higher mammals [ 87 89 ]. Other studies showed that it could induce apoptosis in M12 prostate cancer cell line [ 90 ].…”
Section: Insulin-like Growth Factor Binding Proteins (Igfbps)mentioning
confidence: 99%
“…IGFBP-related protein 1 (or IGFBP-7) has been found to have an important role in the female reproductive system. It was implicated in human endometrial receptivity, folliculogenesis as well as growth, development, and regression of the corpus luteum in higher mammals [ 87 89 ]. Other studies showed that it could induce apoptosis in M12 prostate cancer cell line [ 90 ].…”
Section: Insulin-like Growth Factor Binding Proteins (Igfbps)mentioning
confidence: 99%
“…At present, the biological functions of IGFBP7 are unclear. While it is expressed in a wide variety of human tissues, including gut [ 4 ], it is notably abundant in female reproductive organs such as the mature follicle [ 5 ], the corpus luteum [ 6 ], and the uterus [ 7 , 8 ]. IGFBP7 is present in uterine glandular epithelial cells and stromal cells, particularly during the secretory phase of the menstrual cycle, and IGFBP7 mRNA levels in late secretory stage are approximately 150-fold higher than in the proliferative stage [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…IGFBP7 is ubiquitously expressed in normal tissues and implicated in diverse physiological process including proliferation, adhesion, senescence, and apoptosis [ 8 , 9 ]. In addition, IGFBP7 is abundantly expressed in reproductive organs including blood vessels in the preovulatory follicular wall [ 22 ], granulosa cells of antral follicles [ 23 ], the CL [ 23 , 24 ], and the endometrium [ 25 , 26 ]. Several studies, including ours, have suggested that IGFBP7 functions as a physiological regulator of uterine receptivity [ 25 , 26 ] and follicular steroidogenesis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%